The impact of ethical leadership on environmental performance in the construction industry: mediating role of environmental innovation and innovation climate / Ahmad Khalil AlHawi and Kemal Cek - AlHawi, Ahmad Khalil; Cek, Kemal (Accounting Research Institute (ARI), Universiti Teknologi MARA, Shah Alam, 2024)
While crucial to overall economic growth, the construction industry also has a reputation for significant environmental impacts. There is a pressing need to adopt more environmentally friendly procedures in this sector in light of growing worldwide concerns about sustainability. This study delved into the pivotal role of ethical leadership in influencing environmental performance in the construction industry, particularly within the Kuwaiti context. Leveraging a multi-faceted approach, the study examined the mediating effects of environmental innovation and the overarching innovation climate fostered by ethical leaders. Following a quantitative approach, the hypotheses developed in light of the literature were tested using structural equation modeling (SEM). An empirical survey was conducted among 230 construction industry workers in Kuwait. The results confirm the relationship between ethical leadership and improved environmental performance. Furthermore, both environmental innovation and the broader innovation climate significantly mediated this relationship. The authors suggest further investigation into the role of additional potential variables as mediating and/or moderating factors. Recommendations are also made for the top management of construction firms for their consideration of environmental innovation and the innovation climate, along with the improvement of environmental performance.